MENGADAPTASI PENDIDIKAN 4.0: INTEGRASI ANALISIS BIG DATA DALAM PENGAMBILAN KEPUTUSAN - Ansori, Ahmad; Ulfa, Merrina; Aulia, Puja; Ilham, Rahmat (Universitas Islam Negeri Alauddin Makassar, 2025)
The application of big data in the education sector has emerged as a crucial strategy in addressing the challenges of the Fourth Industrial Revolution. This study responds to the limited integration of big data in academic decision-making processes, particularly within primary and secondary education institutions in Indonesia. The purpose of this research is to systematically examine how big data analytics supports more effective academic decision-making, offering both practical contributions for educational management and theoretical implications for the development of data-driven decision-making models. This study employs a literature Review method which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The literature reviewed includes relevant national and international journal articles on big data and education. The findings reveal that big data plays a significant role in optimizing educational resource management, enhancing the efficiency of learning interventions, and supporting strategic planning based on evidence. Moreover, the study emphasizes the importance of technological infrastructure, human resource competencies, and data protection as key enablers for successful big data integration. The study provides essential insights for policymakers to encourage digital transformation and evidence-based practices in schools.